Non-covalent chemistry of graphene: Electronic communication with dendronized perylene bisimides - Kozhemyakina, Nina; Englert, Jan; Yang, Guang; Spiecker, Erdmann; Schmidt, Cordula; Hauke, Frank; Hirsch, Andreas; Spiecker, Erdmann (Advanced Materials, 2010)
Mutual attraction: π-π bonding promotes electronic interactions between graphene and a π-conjugated perylene in a liquid dispersion. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.